2019
DOI: 10.1093/asj/sjz306
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Fat Extract Increases Dermal Thickness by Enhancing Angiogenesis and Extracellular Matrix Production in Nude Mice

Abstract: Background Although adipose-derived stem cells (ADSCs) and nanofat exert antiaging effects on skin, they contain cellular components that have certain limitations in clinical practice. Cell-free fat extract (Ceffe) is a fraction purified from nanofat through removal of cellular components and lipid remnants that contains various growth factors. Objectives The purpose of this study was to evaluate the effects of Ceffe on cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Then centrifuge at 2000 g for 5 min and filter with a 0.22-μm syringe filter 6. Or after being frozen and thawed for one cycle and centrifuge at 1200 g for 5 min, then filter with a 0.22μm syringe filter Rich in cytokines, but the source is relatively limited VEGF [23][24][25][26] bFGF [24][25][26][27] BDNF [23,27];GDNF [23,27] TGF-β [23,26,27]; HGF [23,26,27]; PDGF [23,26,27]; IGF-1 [80,85]; KGF [28] dimensional culture, ADSC-CM from three-dimensional culture showed a superior stimulatory effect on the proliferation and migration of fibroblasts and keratinocytes and was more effective in promoting wound healing [32]. This was consistent with the finding that galectin-1 was only detected in ADSC-CM from three-dimensional culture, which was found to be an important factor for the migration of keratinocytes [32], as well as to the higher cytokine secretion [44].…”
Section: Adsc-cm and Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Then centrifuge at 2000 g for 5 min and filter with a 0.22-μm syringe filter 6. Or after being frozen and thawed for one cycle and centrifuge at 1200 g for 5 min, then filter with a 0.22μm syringe filter Rich in cytokines, but the source is relatively limited VEGF [23][24][25][26] bFGF [24][25][26][27] BDNF [23,27];GDNF [23,27] TGF-β [23,26,27]; HGF [23,26,27]; PDGF [23,26,27]; IGF-1 [80,85]; KGF [28] dimensional culture, ADSC-CM from three-dimensional culture showed a superior stimulatory effect on the proliferation and migration of fibroblasts and keratinocytes and was more effective in promoting wound healing [32]. This was consistent with the finding that galectin-1 was only detected in ADSC-CM from three-dimensional culture, which was found to be an important factor for the migration of keratinocytes [32], as well as to the higher cytokine secretion [44].…”
Section: Adsc-cm and Wound Healingmentioning
confidence: 99%
“…Deng et al [64] showed that ATE could promote the proliferation of dermal fibroblasts, thereby increasing ECM synthesis and reducing UVB-induced intracellular ROS accumulation through the upregulation of the expression of the antioxidant enzyme glutathione peroxidase (Gpx-1), ultimately exerting antiphotoaging effects. Additionally, Zheng et al [26] observed that the expression of MMP-1 and MMP-3 decreased and that of TIMP1 and TIMP3 increased in nude mice treated with ATE, indicating that ATE could promote ECM production, increase the thickness of the nude mouse dermis, and inhibit collagen degradation.…”
Section: Ate and Skin Agingmentioning
confidence: 99%
“…Given our previous ndings on CEFFE's positive effects on wound healing, [8][9][10][11]15] we examined its effects on injured CNS repair. In the present study, we demonstrated that CEFFE has neuroprotective and axon regenerating effects on injured RGCs, which suggest its potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The CEFFE was prepared in accordance with previously established methods [8][9][10]. Brie y, human adipose tissue was obtained from healthy female donors who underwent liposuction.…”
Section: Ceffe Preparationmentioning
confidence: 99%
“…Plant extracts [ 9 ], antioxidants [ 10 ], growth factors and cytokines [ 11 ], and stem cells [ 12 ] can be used to treat photoaging. Recently, stem cell therapy has attracted great attention because it can improve the regeneration ability of various tissues [ 12 14 ]. It is reported that stem cells and their derivatives are able to ameliorate skin conditions to some extent [ 15 ].…”
Section: Introductionmentioning
confidence: 99%